Analisis Kelayakan Usahatani Kunyit Petani Desa Petiken yang Tergabung Dalam Kelompok Tani BPP Driyorejo Kabupaten Gresik: Analysis of the Feasibility of Turmeric Farming of Farmers of Petiken Village who are Members of the BPP Driyorejo Farmer Group, Gresik Regency - Harya, Gyska Indah; Wahyuningrum, Widya (Jurnal Ilmiah Manajemen Agribisnis, 2023)
The purpose of this study was to analyze the turmeric farming of the BPP Driyorejo farmer group. The stages of this research began with identifying problems with the aim of collecting data and observing and then proceeding with analyzing production costs which then carried out acceptance calculations, R/C ratio analysis and BEP analysis to determine the feasibility of farming in the BPP Driyorejo farmer group. The R/C ratio test obtained a result of 2.6 > 1 so that the farming was said to be feasible, the revenue BEP was 656,598.227 with a total revenue of 7,368,103, of which 7,368,103 > 656,598.227 so that the turmeric farming made a profit. The production BEP calculation is 0.187128 kg where the total production of turmeric is 2105 kg > 0.187128 kg so that this turmeric farming is profitable and feasible to develop. Calculation of the price BEP is IDR 1,341, where the price of turmeric is 3,500 > 1,341 so that the turmeric farming is profitable and feasible to develop.